Financial Dollarization in Latin America - Rennhack, Robert (IMF Working Papers; Working Paper, 2006)
This paper tests several explanations for financial dollarization (FD), with an emphasis on Latin America. The results provide evidence that FD is a rational response to inflation uncertainty. The paper builds on previous research by finding that an exchange rate policy biased towards currency depreciation and currency mismatches tends to contribute to high FD and that FD is highly persistent. These results suggest that countries with significant FD should encourage the use of domestic currency by maintaining macroeconomic stability; allowing more exchange rate flexibility and less bias towards currency depreciation; and adapting prudential regulations to ensure that costs associated with FD are fully internalized in financial contracts. At the same time, restoring confidence in the domestic currency may take many years of sound policies.